AVOID CONTAMINATION IN SOYBEAN (Glycine max, L. [Merrill]) MICROSPORES CULTURE - -, Sumarmi (Proceeding of International Congress, 2014)
Microspore culture is done to obtain pure strains. The purpose of soybean microspore culture to obtainquality seeds. Two important step that must be done is isolation of microspores in starvation medium andsubculture into embryogenesis medium. Many factors contributing to the contamination of soybeanmicrospore culture. Contamination in the B medium temperature 34 0C is more common than 4 0C. Vulnerableto contamination because of embryogenesis medium rich in nutrients. Bacterial contaminationcan be caused by internal contaminants such as shape of the anther. Other internal contaminants thatcause diseases such as fungi Colletotrichum truncatum and Phakopsora pachyrhizi. Antagonistic fungiwhich contaminate cultures that Trichoderma spp., Alternaria spp., Fusarium spp. Handling of contaminationis done by selecting the appropriate methods in order to remain viable microspores. Sterilization soybeanflower buds with 20% Tween for 10 minutes and then rinsed with distilled water. Moreover sterilizationwith 4% Hg Cl2 and 10% NaOCl for 10 minutes, rinsed with distilled water times, followed by 96%alcohol for 1 minute, can press up to 70% contamination.Keywords: soybean, microspore, contamination